2002
DOI: 10.7748/ns.17.12.33.s51
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ use of evidence in pre-operative fasting

Abstract: By reviewing the literature on pre-operative fasting and reflecting on the evidence base for nursing practice, this article aims to offer explanations of why nurses act contrary to evidence which suggests that their practice is outdated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Within this study, the nurses felt that patients should be fasted up to eight hours from solid food and four to six hours from clear fluids. Recent evidence, however, stipulates that patients should only be fasted for four to six hours from solid food and be allowed clear fluids up until two to three hours pre-operatively (Dean and Fawcett 2002). The current study indicated that while the nurses were aware of the rationale behind why a patient needs to fast, there was an apparent lack of awareness regarding up-to-date studies.…”
Section: Discussion and Reflectionmentioning
confidence: 64%
See 2 more Smart Citations
“…Within this study, the nurses felt that patients should be fasted up to eight hours from solid food and four to six hours from clear fluids. Recent evidence, however, stipulates that patients should only be fasted for four to six hours from solid food and be allowed clear fluids up until two to three hours pre-operatively (Dean and Fawcett 2002). The current study indicated that while the nurses were aware of the rationale behind why a patient needs to fast, there was an apparent lack of awareness regarding up-to-date studies.…”
Section: Discussion and Reflectionmentioning
confidence: 64%
“…General anaesthesia has always carried the risk of vomiting during induction, which may lead to serious complications and can even be fatal (Dean and Fawcett 2002). Therefore, it is usual to deny all oral intake for up to four hours, and solid food from four to six hours before surgery (Rowe 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…U nekim bolnicama pacijentov predstavnik poma'e pacijentu da razume situaciju, naro~ito kada le~enje uklju~uje i hirur{ku intervenciju. Uvek kada je to mogu}e lekar treba da bude uklju~en u obja{njavanju situacije pacijentu [30][31][32][33][34][35] .…”
Section: Priprema Za Operacijuunclassified